2019
DOI: 10.2134/agronj2018.08.0535
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Biomass Production in Temperate Agroecozones

Abstract: Cover crop (CC) biomass production dictates agricultural and environmental services that CCs deliver, but finding a review on this topic is difficult. We synthesized published data on CC biomass production for 20 common CC species in temperate regions and discussed factors affecting CC biomass production. Review of 389 papers indicated CC biomass production was 3.37 ± 2.96 Mg ha-1 (mean ± SD). Cover crop biomass production for the top five biomass-producing species was: sorghum (Sorghum sp.) (5.99 Mg ha-1) > s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 61 publications
3
73
3
6
Order By: Relevance
“…Loss of excess nitrates through leaching is an increasing concern due to potential pollution of surface water and groundwater resources. If rye contains about 1.2% N (Kuo, Sainju, & Jellum, 1996) and produces about 4.68 ± 3.66 Mg ha −1 of biomass (Ruis et al, 2019), then about 75 kg ha −1 of N can be removed from the soil for the aboveground biomass alone. For example, a study found that grass CCs, such as rye, grown with 0, 34, 67, or 101 kg ha −1 of N produced about 2.2, 4.11, 4.8, and 6.2 Mg ha −1 of aboveground biomass and contained about 20.8, 33.1, 40.7, and 58.8 kg ha −1 of N (Balkcom, Duzy, Arriaga, Delany, & Watts, 2018).…”
Section: Nutrient or Pollutant Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of excess nitrates through leaching is an increasing concern due to potential pollution of surface water and groundwater resources. If rye contains about 1.2% N (Kuo, Sainju, & Jellum, 1996) and produces about 4.68 ± 3.66 Mg ha −1 of biomass (Ruis et al, 2019), then about 75 kg ha −1 of N can be removed from the soil for the aboveground biomass alone. For example, a study found that grass CCs, such as rye, grown with 0, 34, 67, or 101 kg ha −1 of N produced about 2.2, 4.11, 4.8, and 6.2 Mg ha −1 of aboveground biomass and contained about 20.8, 33.1, 40.7, and 58.8 kg ha −1 of N (Balkcom, Duzy, Arriaga, Delany, & Watts, 2018).…”
Section: Nutrient or Pollutant Removalmentioning
confidence: 99%
“…Also, a brief discussion of the dominant factors that affect both aboveground and belowground CC biomass production is warranted to better understand variability of CC biomass production and sustainability of CC harvest. Ruis et al (2019) reported that CC biomass production in temperate regions ranges from 0.1 to 32 Mg ha −1 (average 3.37 ± 2.96 Mg ha −1 ). Cover crop biomass can be highly variable and site specific, depending on CC management, CC species, cropping system, and climate (i.e., precipitation and temperature).…”
Section: Amount Of Harvestable Cover Crop Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…While pre‐harvest planting did improve CC biomass production at two of three sites in both rotations, it was typically below 1 Mg ha −1 . Other studies in the region observed biomass production of 2.92–4.19 Mg ha −1 depending on species (Nielsen, Lyon, Hergert, Higgins, & Holman, 2015b), 0.26–0.51 Mg ha −1 if terminated in mid‐April, 1.60–2.85 Mg ha −1 if terminated in late April–early May (Ruis et al., 2017), 0.80 Mg ha −1 planted following corn harvest (Blanco‐Canqui et al., 2014), and 1.47 Mg ha −1 if planted in September into corn (Blanco‐Canqui, Sindelar, Wortmann, & Kreikemeier, 2017; Ruis et al., 2019). This means average CC biomass production in the region may be about 1.8 Mg ha −1 , which is above the CC biomass production in our study (<1 Mg ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Planting cover crops in mid‐summer after hay harvest is popular in the Tulelake area because it allows producers to generate crop income while taking advantage of the warm temperatures of summer and early fall for cover crop growth (Ruis et al., 2019). However, incorporation of the cover crop in fall potentially increases the risk of leaching of NO 3 − derived from the cover crop residues below the root zone of the following crop with winter rains.…”
Section: Introductionmentioning
confidence: 99%